The Influence of Food and Beverages in Human Life According to Buya Hamka (Analysis Study of Tafsir Al-Azhar) - Fuady, Rifqy Jauhar; Akmaliyah, Akmaliyah (UIN Sunan Gunung Djati Bandung, 2020)
Al-Quran is a book of life, containing various rules concerning the order of human life in the world and the results of that life in the hereafter. Therefore it is certain that the Quran talks about food. The term food in Arabic is mentioned with 3 pieces of the terms. These are: